Embodied Religious Knowledge in Javanese Sufism: Existential-Practical Hermeneutics and the Formation of Epistemic Authority - Taufikin, Taufikin; Wahyudi, Chafid; Zulkifli Bin Mamat; Badawi, Habib (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2026)
This study examines how embodied religious knowledge is generated in Javanese Sufism through the dynamic interplay of bodily practice, social articulation, and negotiated epistemic authority. Moving beyond interpretations that reduce Sufi Kejawen to a syncretic culture, it investigates how tirakat, selametan, rukun, and unggah-ungguh function as interconnected processes through which embodied religious knowledge is produced, socially articulated, and legitimized. Using a hermeneutic-ethnographic approach, the article was conducted within the Tarekat Qadiriyyah wa Naqshbandiyyah (TQN) community in Indonesia through three months of fieldwork involving 20 participants, in-depth interviews, participant observation, and document analysis. The findings demonstrate that tirakat generates embodied religious knowledge through disciplined bodily practice, while communal rituals transform individual experience into socially recognized meanings that subsequently acquire legitimacy through ongoing negotiation with orthodox Islamic authority. The study proposes existential-practical hermeneutics as an analytical framework explaining how embodiment, social articulation, and negotiated legitimacy constitute an integrated process of epistemic authority formation in Javanese Sufism, thereby advancing scholarship on embodied religion, lived Islam, and contemporary Islamic authority.